Preexisting Carpal and Carpometacarpal Osteoarthritis Has No Impact on Function after Distal Radius Fractures - Davies, Jonah Hébert; Centomo, Hugo; Leduc, Stéphane; Beaumont, Pierre; Laflamme, G.-Yves; Rouleau, Dominique M. (Journal of Wrist Surgery, 2017)
Background Functional outcomes of distal radius fractures vary widely regardless of treatment methods.Purpose This study aims to verify whether preexisting carpal and carpometacarpal (CMC) osteoarthritis (OA) will negatively impact wrist functional outcome in patients with distal radius fractures.Patients and Methods A retrospective case–control study was done using a prospective trauma database. Patients were matched 1:1 in two groups based on the presence of wrist or carpal arthritis (OA). The groups were matched for sex, follow-up, and treatment type. Patients were followed up for a minimum of 1 year and functional outcomes were assessed using validated scores.Results A total of 61 patients were included. Mean age was 63 years (range: 20–85) and average follow-up was 26 months. There were 31 patients in the OA+ group and 30 in the OA− group. Forty-one patients were treated surgically and 20 nonoperatively. None of the patients in the OA− developed OA during follow-up. Both groups were comparable for sex, residual deformity, and follow-up. There was no significant difference for the visual analog scale, Short Form-12, Quick Disability Arm Shoulder Hand, and Patient-rated Wrist Evaluation, or for radiographic outcomes.Conclusion Preexisting OA in the wrist or CMC does not seem to impact outcomes of distal radius fractures, regardless of treatment, age, or sex. Although this is a negative study, the results are important to help counsel patients with distal radius fractures. Further work must be done to identify other potential causes for negative outcomes.Level of Evidence Level III, prognostic study.
Keywords: distal radius fracture; prognostic; factors; carpal osteoarthritis